2010
DOI: 10.1088/0143-0807/31/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional temperature field simulation for the rotor of an asynchronous motor

Abstract: A three-dimensional heat transfer model is built according to the rotor structure of an asynchronous motor, and three-dimensional temperature fields of the rotor under different working conditions, such as the unloaded, rated loaded and that with broken rotor bars, are studied based on the finite element numerical method and experiments. The feasibility of inspecting the motor faults by infrared thermography is also discussed. The following conclusions can be drawn from the study: the temperature field is unif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…4 The slove region for stator 3-D temperature field analysis Fig. 5 Temperature sensor embedment of stator winding Solving region basic assumptions made as follows [7][8]: 1) Due to the circumferential symmetry, the center of stator tooth surface is adiabatic;…”
Section: Advanced Materials Research Vol 462mentioning
confidence: 99%
“…4 The slove region for stator 3-D temperature field analysis Fig. 5 Temperature sensor embedment of stator winding Solving region basic assumptions made as follows [7][8]: 1) Due to the circumferential symmetry, the center of stator tooth surface is adiabatic;…”
Section: Advanced Materials Research Vol 462mentioning
confidence: 99%
“…Zhang et al [5] concluded from research that the ambient and cooling temperatures under the action of forcing factors affect the temperature rise of forced water-cooled motors. Ding et al [6] utilized a 55-kW ship-driven asynchronous motor as an example, the three-dimensional steady-state temperature field was calculated using the finite volume element method. The temperature rise characteristics of the motor's main parts during rated load operation were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…(2) the second boundary condition, the heat exchange keeps constant on the boundary (including heat exchange interface); (3) the third boundary condition, the temperature of the surrounding medium and the convection coefficient on the boundary are known. According to the boundary conditions above, the solution of heat conduction differential equation [5] can be summarized as one boundary condition question, as in ( )…”
mentioning
confidence: 99%